Sustainable synthesis of polymer-grade ethylene via electrified acetylene semihydrogenation - Zihao Yan; Libang Xu; Huiyuan Zhu (Proceedings of the National Academy of Sciences, 2025)
The electrocatalytic semihydrogenation of acetylene (C 2 H 2 ), powered by renewable electricity, provides an energy- and cost-efficient alternative to conventional thermocatalytic methods for purifying crude ethylene (C 2 H 4 ) streams. This approach provides a more sustainable route to polymer-grade C 2 H 4 by reducing greenhouse gas emissions, yet its commercial potential remains limited by the scarcity of high-performance catalysts and the absence of comprehensive techno-economic analyses for large-scale implementation. In this study, we conduct an extensive screening and evaluation of monodisperse metal nanoparticle (NP) catalysts (Cu, Ag, Au, Pd, Bi) with tunable particle sizes and morphologies for the electrocatalytic semihydrogenation of C 2 H 2 in flow reactors. Among these candidates, 45 nm Cu nanocubes and 8 nm Ag NPs exhibited the highest performance. In a simulated crude ethylene stream (C 2 H 2 : C 2 H 4 = 1:80), Cu nanocubes achieved 99.7% C 2 H 2 removal at room temperature with a specific selectivity of 86.7% for C 2 H 4 and maintained stability for 120 h. Meanwhile, 8 nm Ag NPs exhibited a high specific selectivity of 98.9%, with 96.7% conversion and 24-h stability under the same conditions. A detailed techno-economic analysis confirms the feasibility of electrocatalytic systems for industrial-scale crude ethylene treatment, with an optimal conversion cost of $0.74 per kg of C 2 H 2 , compared to $1.34 per kg for the optimized thermocatalytic system. Furthermore, our life cycle assessment highlights the environmental benefits of the electrocatalytic pathway with a carbon emission reduction of over 50%. Our electrified, efficient C 2 H 2 semihydrogenation in C 2 H 4 crude streams minimizes environmental impact and optimizes resource use, contributing to a more sustainable future.